Stowarzyszenie jako przykład instytucjonalizacji w kreowaniu wizerunku przedsiębiorstwa agroturystycznego - Bodak, Andrzej; Jagoda, Agnieszka; Pietroń-Pyszczek, Agata (Association as An Example of Institutionalization in Creating the Image of a Farm Tourism Company, 2006)
The article points out the activities which are significant for creating the farm tourism company image. Taking Polish conditions of such companies functioning into account, the authors would like to stress the usefulness of forming farm tourism groups (associations). The activity of "Sudeckie Towarzystwo Turystyki Wiejskiej" (Sudetic Association of Farm Tourism) has been verified.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 98-102